Intratumoural heterogeneity and clone evolution of oral squamous cell carcinoma. Issue 11 (25th August 2021) - Wang, Lin; Wang, Xinmiao; Jia, Yulin; Guo, Fengyuan; Zhengjun, Shang; Shao, Zhe
Abstract: Oral squamous cell carcinoma (OSCC) is the most common type of oral malignancy. Our study uses multipoint materials to explore the heterogeneity and metastasis mechanism of OSCC to find more accurate molecular markers and new therapeutic targets. By using whole‐exome capture and sequencing and tumor evolution analysis, we found that most clone‐driven mutations were located in the branches of tumor phylogenetic tree, such as COTL1, CASP8, and PROCR. Most clone‐driven OSCC mutations occur mainly in tumor suppressor genes, including TP53, SFRP4, and NOTCH1. Our study on intratumor heterogeneity (ITH) and clonal evolution provides an important molecular basis for further understanding of OSCC occurrence and development and metastasis and provides potential targets for the treatment of this disease.